PENGARUHKELOMPOKREFERENSIDANGAYAHIDUPTERHADAPKEPUTUSANMENGGUNAKANBLACKBERRY THEEFFECTSOFLIFESTYLEANDREFERENCEGROUPONDECISIONOFUSINGBLACKBERRY - Evanina Sianturi; Erida .; Ade Titi Nifita (Konsentrasi Manajemen Pemasaran Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2012)
TheresearchaimsistoexplaintheeffectofthesimultaneousandpartialoflifestyleandreferencegrouponBlackBerrypurchaseandexplainthedominantfactoreffects.Samplessizeconsistsof96units,whicchousenfromEconomicFacultyStudents.Analysisusesdescriptiveandstatisticalanalysistorevealthestatisticalpattern.Theresultsshowsthatthepercentagecontributionofindependentvariablesthereferencegroup(X1)andlifestyle(X2)onthedependentvariable(thedecisionofusingBlackBerry(Y)is41%.Hence,itisrecommendedthattheBlackBerryCorporationuisesreferencegroupsandlifestylestobeoneofthemarketingtool.Keywords:decisionofusing,referencegroupandlifestyle